Extraction of circulating endogenous gastrin by the gastric fundus. Issue 2 (February 1974) - Evans, John C. W.; Reeder, David D.; Becker, Horst D.; Thompson, James C.
Abstract : The effect of circulatory transit of the gastric fundus on serum levels of endogenous gastrin measured directly by radioimmunoassay has been studied in 14 dogs. Gastrin was measured in samples obtained simultaneously from the arterial inflow and venous outflow of the gastric fundus. During basal conditions, transit of the gastric fundus resulted in no change in gastrin concentration. During periods of stimulated gastrin release from the antrum, nine of the 14 dogs demonstrated a significant gastric acid secretory response. In these dogs there was a significant arteriovenous difference (approximately 30%) in circulating gastrin values. In the remaining five dogs, which did not demonstrate a significant gastric acid secretory response, there was no arteriovenous difference in circulating gastrin values. It is concluded that the gastric fundus is an important site for the inactivation of stimulated levels of circulating gastrin.